Nanoglass and Nanocrystallization Reactions in Metallic Glasses - Perepezko, John H; Gao, Meng; Wang, Jun-Qiang (Frontiers in Materials, 2021)
Strategies to change the properties of metallic glass by controlling the crystallization and the glass transition behavior are essential in promoting the application of these materials. Aside from changing the composition approaches to stabilize the glass and frustrate the nucleation and growth of crystals, new strategies at a fixed glass composition are of special interest. In this review, some recent work is summarized on new strategies to tune the properties of metallic glasses without changing composition. First, the nanocrystallization strategy is introduced that is based on the nanocrystallized microstructures such as those that develop in marginal Al-based metallic glasses. The heterogeneous and transient nucleation effects in the nanocrystallization reactions in Al-based metallic glasses are systematically investigated and can be assessed by the determination of delay time based on Flash DSC measurements. These results provide a basis to understand the strong effect of minor alloying additions on the onset of primary Al nanocrystallization and to design the novel Al-based composites with improved properties. Secondly, by an optimal annealing treatment, a liquid-cooled Au-based metallic glass can achieve very high kinetic stability to yield a large increase in glass transition temperature of 28 K and this is 3-5 times larger than the increase usually reported. The measured enthalpy decrease is about 50% of the difference between the as-cooled glass and the equilibrium crystalline state and reaches the extrapolated enthalpy of the supercooled liquid. Finally, the nano-glass strategy makes an Au-based nanoglass show ultrastable kinetic characters at low heating rate (e.g., 300 K/s) compared to a melt-spun ribbon, which is attributed to the kinetic constraint effect of nanoglobular interfaces. These results indicate that the nanoglass microstructure can act to increase metallic glass stability and provide another mechanism for the synthesis of ultrastable glass. These developments open new opportunities to improve the stability and properties and largely increase the application potentials of metallic glasses.